Outcomes of a Pharmacist-Managed Heart Failure Medication Titration Assistance Clinic. Issue 8 (August 2018) - Bhat, Shubha; Kansal, Mayank; Kondos, George T.; Groo, Vicki
Background: National guidelines recommend angiotensin-converting enzyme (ACE) inhibitors or angiotensin-receptor blockers (ARBs) and β-blockers (BBs) at target doses for morbidity and mortality benefits in heart failure with reduced ejection fraction (HFrEF); regardless, titration of these therapies in practice remains suboptimal. We implemented an outpatient pharmacist-managed HFrEF medication titration assistance clinic (MTAC) at one institution to improve titration for general cardiology (GC) patients.Objective: To evaluate MTAC impact by determining the proportion of patients on target or maximum tolerated ACE inhibitor/ARB and BB doses.Methods: A retrospective chart review of adult patients with documented ejection fraction ≤40% managed in the MTAC or GC from 2011 to 2013 was conducted. HFrEF medication regimens were collected at initial visit and months 1, 2, 3, 6, 9, and 12 to assess titration. Target doses were defined per guideline or dose at which ejection fraction recovered during the study. Maximum tolerated doses were defined as the highest dose patients tolerated without physiological limitations.Results: Of 148 patients, the MTAC managed 51 and GC managed 97. At baseline, 90% of MTAC versus 82% of GC patients were prescribed ACE inhibitors/ARBs and BBs. In the MTAC, 4% were at target or maximum tolerated doses compared with 32% of GC patients ( P < 0.001). At 12 months, 95% of patients in the MTAC and 87% in GC were prescribed ACE inhibitors/ARBs and BBs. Of those prescribed ACE inhibitors/ARBs and BBs, 64% in the MTAC versus 40% in GC reached target or maximum tolerated doses ( P = 0.01).Conclusions: The pharmacist-managed MTAC increased the proportion of patients on optimal HFrEF therapies and are a resource for GC patients.